The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/molecules26226895
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Based Colloidal Delivery Systems for Bioactives

Abstract: The supplementation of plant-based foods and beverages with bioactive agents may be an important strategy for increasing human healthiness. Numerous kinds of colloidal delivery systems have been developed to encapsulate bioactives with the goal of improving their water dispersibility, chemical stability, and bioavailability. In this review, we focus on colloidal delivery systems assembled entirely from plant-based ingredients, such as lipids, proteins, polysaccharides, phospholipids, and surfactants isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 118 publications
0
11
0
Order By: Relevance
“…Regarding natural proteins, whey proteins and caseins from bovine milk have been widely used as emulsifiers, as they are effective for the stabilisation of emulsion-based systems [ 97 , 98 , 99 ]. Recently, some researchers have focused on the use of plant-based proteins such as those from peas, lentils, or rice, to stabilise emulsion-based delivery systems since they are better for human health, the environment, and animal welfare [ 100 ]. As an example, some authors have reported that despite being a poorly soluble protein, pea protein can be used to stabilise vitamin-D-loaded nanoemulsions after a pH-shifting and sonication treatment [ 101 ].…”
Section: Natural-based Stabilisers For Emulsion-based Delivery Systemsmentioning
confidence: 99%
“…Regarding natural proteins, whey proteins and caseins from bovine milk have been widely used as emulsifiers, as they are effective for the stabilisation of emulsion-based systems [ 97 , 98 , 99 ]. Recently, some researchers have focused on the use of plant-based proteins such as those from peas, lentils, or rice, to stabilise emulsion-based delivery systems since they are better for human health, the environment, and animal welfare [ 100 ]. As an example, some authors have reported that despite being a poorly soluble protein, pea protein can be used to stabilise vitamin-D-loaded nanoemulsions after a pH-shifting and sonication treatment [ 101 ].…”
Section: Natural-based Stabilisers For Emulsion-based Delivery Systemsmentioning
confidence: 99%
“…Over the past decade or so, there has been a great deal of interest in developing colloidal delivery systems that can encapsulate, protect, and release bioactive substances, such as drugs, nutrients, and nutraceuticals [ 1 , 2 , 3 ]. To be suitable for commercial applications, these delivery systems should be fabricated from affordable and label-friendly food ingredients using cost-effective and sustainable manufacturing operations that are capable of being scaled up [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some types of starch are rapidly hydrolyzed by amylase in the mouth and small intestine, while most other polysaccharides, collectively known as dietary fibers, are not digested but can be fermented by the prebiotic bacteria (e.g., inulin, pectin, psyllium) [ 44 , 45 ]. This can allow the use of biopolymer hydrogels to prolong the satiety effect of foods, and more importantly to enhance the gastrointestinal stability of bioactive compounds they can be carrying [ 46 ]. Some applications of biopolymeric hydrogels are highly interdisciplinary (drug delivery system, matrix for tissue culture, etc.).…”
Section: Introductionmentioning
confidence: 99%